2004
DOI: 10.1177/156482650402500102
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Successful Micronutrient Programs Part I: Program Initiation

Abstract: Internationally recognized research findings on the potential health benefits of preventing micronutrient deficiencies--especially reduced child mortality from vitamin A deficiency and prevention of in utero developmental damage and mental retardation from iodine deficiency--have contributed to raising the awareness of deficiencies and the commitment of many governments to their reduction or near-elimination. The procedures undertaken to decide on large-scale programs followed conventional patterns in the 12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…(1) On the other hand, the difficulties in producing normative data in a developing country are well known and only a sample from the upper strata of the population will suit the recommendations of the World Health Organization (WHO) for obtaining reference values. (13, 14, 15) We believe that the reliability of the data in our study is high, due to the longitudinal design of the study and also due to the fact that the subjects consisted of the upper strata of the population. It must be added that the mixed population of Istanbul city is quite representative of the whole of Turkey.…”
Section: Discussionmentioning
confidence: 81%
“…(1) On the other hand, the difficulties in producing normative data in a developing country are well known and only a sample from the upper strata of the population will suit the recommendations of the World Health Organization (WHO) for obtaining reference values. (13, 14, 15) We believe that the reliability of the data in our study is high, due to the longitudinal design of the study and also due to the fact that the subjects consisted of the upper strata of the population. It must be added that the mixed population of Istanbul city is quite representative of the whole of Turkey.…”
Section: Discussionmentioning
confidence: 81%
“…The design of the studies summarized in this paper largely conforms to the criteria suggested by Waterlow and adopted by WHO, requiring that the reference population be well-nourished, the sampling procedure clearly defined and reproducible, the sample of adequate size, the measurements relevant and of good quality, and the data adequately treated. WHO also recommends that measurements be taken at one month intervals in early infancy ( 17 , 18 , 19 , 20 ). In view of the fact that in Turkey, a country where large differences in economic means and lifestyle still exist among SEC, a nationally representative sample would be likely to include many children whose health has been compromised by unfavorable economic, educational, and environmental conditions and not reflect the growth potential of the population, the study population is a selective one and consists of children of well to do families.…”
Section: Discussionmentioning
confidence: 99%
“…However, iron supplementation programs tend to be less well developed than programs aimed at other micronutrients, such as iodine or vitamin A. As a result, limited data are available on iron supplementation programs at the international level [16], and we were unable to find any recent global reviews on how many countries have such programs.…”
Section: Micronutrient Supplementation Programsmentioning
confidence: 96%
“…Coverage is reasonably equitable in Nigeria and Ethiopia, but in India there are marked inequalities. India used to have a nationwide law for salt iodization, but this legislation was subsequently rescinded, and the adoption and enforcement of laws governing salt iodization is now decided at the state level [16]. Kits for testing iodine content in salt are accurate for showing the presence of any iodine and relatively inaccurate for measuring quantity [17].…”
Section: S9mentioning
confidence: 99%